The Physics and Applications of High Brightness Electron Beams 2003
DOI: 10.1142/9789812705235_0027
|View full text |Cite
|
Sign up to set email alerts
|

Energy Loss of a High Charge Bunched Electron Beam in Plasma: Analysis

Abstract: There has been much interest in the blowout regime of plasma wakefield acceleration (PWFA), which features ultra-high fields and nonlinear plasma motion. Using an exact analysis, we examine here a fundamental limit of nonlinear PWFA excitation, by an infinitesimally short, relativistic electron beam. The beam energy loss in this case is shown to be linear in charge even for nonlinear plasma response, where a normalized, unitless charge exceeds unity. The physical basis for this effect is discussed, as are devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In 1980s, authors have set up basic 1-D theories on these two conceptions [12][13][14]. Then, during following decades, a lot of investigations have been addressed to various wakefieldrelated problems [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In 1980s, authors have set up basic 1-D theories on these two conceptions [12][13][14]. Then, during following decades, a lot of investigations have been addressed to various wakefieldrelated problems [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4 In this regime, a relativistic beam (the drive bunch) produces large-amplitude wake-fields in a plasma of density n 0 much less than the drive beam density n b . The high charge of the drive bunch causes plasma electrons in its wake to be expelled from the beam path, producing a rarified ion column behind the bunch.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that this result holds true even when the drive beam charge is large enough to cause the plasma electron motion to be relativistic [5].…”
Section: Introductionmentioning
confidence: 85%
“…The PWFA in the blowout regime is an extremely nonlinear system, and in order to systematically understand it, we must first investigate the coupling of energy from the drive beam into the plasma. This phenomenon has been analyzed recently, with a focus on the question of the saturation of the plasma response for very high charge [5]. Further, because it depends on fewer experimental variables, the energy loss can be a particularly good diagnostic of the nonlinear beam-plasma interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation